Co-transcriptional gene regulation in eukaryotes and prokaryotes - Shine, Morgan; Gordon, Jackson; Schärfen, Leonard; Zigackova, Dagmar; Herzel, Lydia; Neugebauer, Karla M. (Nature reviews. Molecular cell biology, 2024)
Many steps of RNA processing occur during transcription by RNA polymerases. Co-transcriptional activities are deemed commonplace in prokaryotes, in which the lack of membrane barriers allows mixing of all gene expression steps, from transcription to translation. In the past decade, an extraordinary level of coordination between transcription and RNA processing has emerged in eukaryotes. In this Review, we discuss recent developments in our understanding of co-transcriptional gene regulation in both eukaryotes and prokaryotes, comparing methodologies and mechanisms, and highlight striking parallels in how RNA polymerases interact with the machineries that act on nascent RNA. The development of RNA sequencing and imaging techniques that detect transient transcription and RNA processing intermediates has facilitated discoveries of transcription coordination with splicing, 3′-end cleavage and dynamic RNA folding and revealed physical contacts between processing machineries and RNA polymerases. Such studies indicate that intron retention in a given nascent transcript can prevent 3′-end cleavage and cause transcriptional readthrough, which is a hallmark of eukaryotic cellular stress responses. We also discuss how coordination between nascent RNA biogenesis and transcription drives fundamental aspects of gene expression in both prokaryotes and eukaryotes. Methodological advances have enabled discoveries of RNA polymerase interactions with RNA processing machineries, such as the splicing and 3′-end cleavage machineries. This Review discusses the roles of these interactions in gene regulation and eukaryotic cellular stress responses, and highlights parallels between co-transcriptional RNA processing in eukaryotes and prokaryotes.